2021
DOI: 10.1080/08870446.2021.1941961
|View full text |Cite
|
Sign up to set email alerts
|

Benefit finding moderates the relationship between young carer experiences and mental well-being

Abstract: Objective: Research has shown that some young carers face many negative consequences because of their caring experiences, whereas others seem to be unaffected or even report greater well-being. To understand how caring for a family member or close friend can have these different effects, this study compared benefit finding between young carers and their peers and examined its association with mental well-being. Design: We recruited 2,525 adolescents aged 15-21 years (59.6% female, M age = 17.73) through the Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
10
1
Order By: Relevance
“…The indirect paths were solely negative, as there was an indirect association over perceived helplessness, but no association over subjective coping. These exploratory findings appear to be important since feeling more empathetic with others is a previously described characteristic of young carers (e.g., Stamatopoulos 2018;Wepf et al 2021) and will therefore need further attention.…”
Section: When Is Benefit Finding Associated With Mental Well-being In Young Carers?mentioning
confidence: 85%
See 1 more Smart Citation
“…The indirect paths were solely negative, as there was an indirect association over perceived helplessness, but no association over subjective coping. These exploratory findings appear to be important since feeling more empathetic with others is a previously described characteristic of young carers (e.g., Stamatopoulos 2018;Wepf et al 2021) and will therefore need further attention.…”
Section: When Is Benefit Finding Associated With Mental Well-being In Young Carers?mentioning
confidence: 85%
“…Data were derived from a survey completed by 2525 adolescents (ranging from 15 to 21 years) recruited through different educational institutions in the German-speaking part of Switzerland during 2018 and 2019 (see also Wepf et al 2021). Informed consent was obtained from all participants via an online form and the institutional Ethics Committee from the Faculty of Arts and Social Sciences of the University of Zurich approved the project procedures.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The possible protective roles of several other traits have also been revealed. These traits typically involve a positive attitude toward the future (eg, hope, 38 optimism, 53 , 64 positive expectancy, 30 reward sensitivity 34 ), a positive attitude toward oneself (eg, self-efficacy, 64 self-esteem, 53 , 64 self-compassion, 33 internal locus of control, 31 perceived control, 24 , 53 problem-solving coping style, 17 sense of ethnic identity 25 ), or the tendency to see positives or meaning in one’s life (eg, trait benefit-finding, 61 sense of coherence, 69 meaning-focused coping style, 54 sense of life meaning, 18 belief in a just world 27 ). The Big Five personality traits have also been examined as resilience resources, with evidence that Neuroticism exacerbates the negative impact of stressors on positive affect, while the other four traits (especially Conscientiousness and Extraversion) mitigate this impact.…”
Section: Discussionmentioning
confidence: 99%
“…In a longitudinal study of over 1200 Swiss employees, Udayar et al 59 found that work stress at baseline positively predicted work stress 12 months later across all participants, but baseline work stress negatively predicted 12-month life satisfaction only in those with an “oversensitive” personality profile, characterised by lower levels of extraversion and conscientiousness , and higher levels of neuroticism . In a study of over 2500 Swiss students in secondary school or vocational training, Wepf et al 61 found that the experience of being a carer (for a relative or close friend with a health problem) was negatively correlated with mental wellbeing only in those with lower levels of “ trait benefit-finding ” (ie, the disposition to perceive positive changes following adversity). In a longitudinal study of 237 Hong Kong-based university students, Lai and Mak 53 found that daily hassles (in the university student context) over a one-month period predicted lower mental wellbeing only among those with low baseline levels of optimism, self-esteem , and perceived control .…”
Section: Positive Affect As An Outcome Measure Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation